2021
DOI: 10.1107/s160057672100265x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of non-negative matrix factorization for rapid assessment of large sets of atomic pair distribution function data

Abstract: The use of the non-negative matrix factorization (NMF) technique is validated for automatically extracting physically relevant components from atomic pair distribution function (PDF) data from time-series data such as in situ experiments. The use of two matrix-factorization techniques, principal component analysis and NMF, on PDF data is compared in the context of a chemical synthesis reaction taking place in a synchrotron beam, applying the approach to synthetic data where the correct composition is known and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…This often corresponds to a real physical situation (for example, spectra tend to be positive, as are the weights of chemical constituents). As a result we are finding that the mathematical decomposition often results in interpretable, physically meaningful, components and weights, as shown by Liu et al for PDF data [207]. An extension of this showed that in a spatially resolved study, NMF could be used to extract chemically resolved differential PDFs (similar to the information in EXAFS) from non-chemically resolve PDF measurements [208].…”
Section: Applicationsmentioning
confidence: 96%
“…This often corresponds to a real physical situation (for example, spectra tend to be positive, as are the weights of chemical constituents). As a result we are finding that the mathematical decomposition often results in interpretable, physically meaningful, components and weights, as shown by Liu et al for PDF data [207]. An extension of this showed that in a spatially resolved study, NMF could be used to extract chemically resolved differential PDFs (similar to the information in EXAFS) from non-chemically resolve PDF measurements [208].…”
Section: Applicationsmentioning
confidence: 96%
“…8 (after masking the Ni region. 2 ), and extract components that are physically-significant, along with the weight matrix [9]. These can then be used as an important set of QoIs.…”
Section: Mapping Global Similarities and Principle Component Reconstr...mentioning
confidence: 99%
“…Like Pearson analysis, NMF is useful for an exploratory analysis when one does not have prior knowledge on the chemistry or structure of a system [9]. It is related to principle component analysis (PCA) but seems to produce (mathematical) components that explain the variability of the data in the set of PDFs that are more physically meaningful [51], and in particular of interest here, when applied to PDF data [9]. We note that PDF data goes negative, and therefore requires shifting to positive values for this procedure.…”
Section: Mapping Global Similarities and Principle Component Reconstr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-negative matrix factorization (NMF) (Paatero & Tapper, 1994) has been a particularly useful, reliable and intuitive unsupervised machine learning (ML) approach for analytically reducing large datasets of physical signals to reveal trends (Brunet et al, 2004;Pauca et al, 2006). More specifically, it can yield isolated structural signals and their relative presence for both PDF (Liu et al, 2021;Geddes et al, 2019) and powder diffraction (Long et al, 2009) data.…”
Section: Introductionmentioning
confidence: 99%